READING AUTHENTIC MATERIALS TO ENHANCE STUDENTS’ VOCABULARY MASTERY - Vera Nurlia (Journey: Journal of English Language and Pedagogy, 2023)
This study aimed to gather empirical proof of how well reading authentic materials can help students with their vocabulary mastery of procedure text. This study attempted to determine how effective authentic materials aid students' vocabulary mastery of procedure text in order to obtain more information about the result. The research type of this study was quantitative research with a quasiexperimental study design. The instrument used was a vocabulary test. There were 20 multiple-choice questions on this test. 70 students made up the entire participant for this study. SPSS 22 was used to calculate the results of this study. The test of hypotheses revealed that alpha (α) was 0.05 and sig.2-tailed tailed (p) was 0.003. To put it another way, it indicates that the Ha (Alternative Hypothesis) is accepted while the H0 (Null Hypothesis) is rejected. It demonstrated the beneficial impact of using real materials on students' vocabulary retention of procedure text. The number of English words that students knew and could use in their daily activities improved as a result of their reading of authentic texts. The students also exhibited a greater desire to read. Students can use non-linguistic cues like layout, images, shades, signs, and the environment to their advantage.